Utilization of Industrial Excess Heat for CO2 Capture: Effects on Capture Process Design and District Heating Supply - Eliasson, Åsa; Fahrman, Elin (Chalmers tekniska högskola / Institutionen för rymd-, geo- och miljövetenskap, 2020)
Carbon capture and storage (CCS) has been identified as a technology necessary to mitigate climate change and reach the 2°C target of the Paris agreement. Utilization of industrial excess heat is a way to make investments in CCS more feasible. However, in Sweden, industrial excess heat is often utilized for district heating. Thus, CCS may compete with district heating for utilization of industrial excess heat. This thesis evaluates the potential of operating a CCS plant on excess heat from an industrial plant, that is currently utilized for district heating. A techno-economic assessment is performed to discuss design and operational modes of the capture plant. Two industrial plants are investigated as case studies, Preem’s refinery in Gothenburg and the SSAB steel mill in Luleå. Two operational modes are investigated, a seasonally varying (SV) operation and a constant load (CL) operation. If CCS is prioritized over district heating, i.e. excess heat is utilized for CCS without considering the district heating supply, 9.7% and 25.5% of the initial excess heat could be recovered for district heating after capture, for the steel mill and the refinery case respectively. The different properties of the flue gas from the two cases and the process configuration of the capture plant are important to the heat recovery potential from the capture plant. If the district heating delivery is retained, by operating the CCS plant on either the excess heat not utilized for district heating or on primary energy, 17% of the direct CO2 emissions of the steel mill plant is avoided in SV and CL. The SV operation results in that 99% of the total amount of captured CO2 is also avoided. The corresponding figure for the CL operation is 93%. The two operational modes yield comparable costs, however, the SV operation is deemed most viable, since it avoids the use of primary energy, and provides a flexibility in being able to scale-up CCS operation in the future. By evaluating the economic performance of the steel mill capture plants from ...